Ein Kurzschwert - Dolch mit dreieckiger Griffplatte aus Istrien - Mihovilič, Kristina (Arheološki vestnik, 2001)
The article offers a review of short swords - daggers with triangular hilts. In Istria they mostly come from Urnfield cemeteries and represent the typologically latest form (9th and 8th centuries BC) of weapons of northern Italian provenience from the end of the early Bronze Age. The author also discusses the short sword from GromaËica near Loparje on the island of Rab, which differs typologically from the Istrian examples.